Surgical outcomes of partial ciliary body direct suturing under the scleral flap for traumatic cyclodialysis cleft: A five-case series. Issue 6 (November 2022) - Kijima, Riki; Shinmei, Yasuhiro; Shinkai, Akihiro; Kanaya, Rina; Chin, Shinki; Ishida, Susumu
Background: Cyclodialysis cleft is an uncommon finding due to blunt ocular trauma. A larger and more chronic cyclodialysis requires surgical repair. The aim of this study was to introduce a minimally invasive suturing technique for the lens-sparing repair of traumatic cyclodialysis cleft and evaluate outcomes. Methods: This study was a retrospective case series. The medical and surgical records of five patients with traumatic cyclodialysis cleft who underwent this surgery were reviewed. The surgeon (Y.S.) dissected a fornix-based conjunctival flap and created a 90° circumferential and limbal-based scleral flap. Several small incisions parallel to the limbus were made within the scleral bed 1.5 and 3 mm posterior to the limbus. After suprachoroidal fluid drainage, tiny bumps in the ciliary body were exposed from the incisions and sewn directly onto the scleral bed with 10-0 nylon sutures. Results: The mean age of the patients was 37.8 ± 1.3 years. The mean duration from injury to surgery was 14.8 ± 16.7 months. Mean best-corrected visual acuity (BCVA) was 0.56 ± 0.70 and intraocular pressure (IOP) was 5.2 ± 1.9 mmHg. In all patients, IOP normalized and BCVA then returned to baseline following this procedure. Mean postoperative BCVA was 1.17 ± 0.86 and IOP was 17.8 ± 1.3 mmHg. Mean IOP and BCVA recovery times were 82.0 ± 139.6 and 294.3 ± 284.3 days, respectively. Conclusions: Partial ciliary body direct suturing under the scleral flap is a less invasive surgical option without lensectomy and considered safe and effective as a primary surgical repair for traumatic cyclodialysis cleft.